The Steel Industry and The Development Of Local Community: Case Study of Tembo Steel Industry in Kasolo Division Iganga District. - Kibirige, Eriasafu (Kabale University, 2024)
This study assessed the relationship between the steel industry and the development of the community of Kasolo division, Iganga district. The objectives of the study were; to examine the contributions of the Tembo steel industry towards the development of the community around it and to examine the Challenges faced by the community around the Tembo Steel Industry. A cross-sectional survey design was used. Self-administered questionnaires and interview guides were used in data collection and data was analyzed using Excel, a computer software to generate descriptive statistics such as frequencies and percentages and were presented in tables and text and a sample size of 214 respondents was used in the study. The findings on contributions of Tembo Steel Industry, the responses were obtained from the statements that were given to respondents as follows; it provides employment opportunities to people like; drivers, engineers, cleaners and accountants, it is strengthening the economy through paying tax that are used to provide social services like medical, security and transport, transformation of agriculture from use of rudimentary tools to modem machines which increase productivity and the extraction of steel products generates significant foreign exchange and according to the research findings the study went ahead to find the challenges faced by the local community in Kasolo division around Tembo steel industry and responses were obtained from statements that it has caused environmental drawbacks which include; pollution of air, water and soil, accidents that lead to workers losing their limbs, fingers, sight and respiratory disorders, increased theft of steel materials in search for materials like saucepans, goal posts and road signs and displacement of people due to need of land for expansion of the steel plant. The study recommends that; the government should intervene by providing free grounds for people to live in if good health is to be attained the people near Tembo Steel Industry, there should be construction of a hospital in the area to cater to those from Tembo Steel Industry to maintain good health of the people and on areas for further research, further research should be on the same topic but on another industry, Quality of steel products on construction and the effect of steel industry on the environment.